Implementasi Strategi Nasional Partai NasDem Di Jawa Tengah Dalam Pemilu 2014 - Iswandi .; Suwanto Adhi; Fitriyah . (Journal of Politic and Government Studies, 2014)
ABSTRACTDemocratic party this time the main attraction for the emergence of new political parties. The most phenomenal party NasDem. Given, this party is the only party that pass the verification as a new participant in the 2014 election as a new political presence NasDem certainly reasonable if it raises a lot of questions and doubts about efforts to win legislative elections 2014. It’s still not strong mass base owned by NasDem . Therefore NasDem struggled to garner support to parts of the country, including in Central Java. Central Java Central Java NasDem as a new political party will offer what? whether it offers it is something new, or something old that ever offered by other parties. Not to mention, on one hand, given the central Java was PDI-P base which also has the same ideology with NasDem, whether a barrier or facilitate NasDem Java in garnering support.KeywordsPolitical Strategy, Victory Party, NasDem, Central Java NasDem :p